As fronteiras do outsourcing numa 4PL - Sanganha, Miguel Nobre Batista (2011)
Submitted by Bruno Marçal (bruno.marcal@iscte.pt) on 2011-03-28T14:51:49Z No. of bitstreams: 4 RESUMO . ABSTRACT.doc: 39424 bytes, checksum: bb780264c1ee0c5a90d4412fe21d05c4 (MD5) 3. CORPO DO TRABALHO.pdf: 1211562 bytes, checksum: a61e57b41618854058930a4f5ac8c249 (MD5) 2. ÍNDICE.pdf: 144822 bytes, checksum: 35355a8719ea556fe3c6b0e6a1e610ee (MD5) 1. CAPA E AGRADECIMENTOS.pdf: 84693 bytes, checksum: 8599efc2c22e6e8fb60b44c7c2ec8671 (MD5)